The perception of health councilors on access to information and digital inclusion - Fernandes, Violeta Campolina [UNESP]; Spagnuolo, Regina Stella [UNESP]; Nascimento, Edinalva Neves (Univ Sao Paulo, Fac Saude Publica, 2017)
This study is part of the context of the digital inclusion of health counselors and the strengthening of their practices. The objective was to know the perception of municipal health counselors in relation to the access to health information and digital inclusion of a medium sized city in Sao Paulo, Brazil. This is a qualitative research, based on the case study method conducted with sixteen tutelary health counselors. The interview was performed using a semi-structured guide and the data were evaluated in the light of Content Thematic Representational Analysis. The discussion was grounded on the theoretical frameworks of the Theory of Participatory Democracy and the principles of the Unified Health System with emphasis on the policy of Community Participation. It was evidenced an insufficiency of continuing education for directors both in the area of social control as digital inclusion. It is still incipient the access to information in the field of health by digital means, with the unfolding of democratic and participatory embrittlement of the board. There may be some control of those who have better knowledge on health policy information. The members recognize the importance of digital inclusion and want to be included. It was concluded that there are gaps in the access to health information and a fragile digital insertion, which can compromise the recognition and effectiveness of community participation in public health decisions.
Keywords: Information Technology; Health Councils; Social Participation; Information; Internet; Digital Inclusion